2019
DOI: 10.2166/hydro.2019.008
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of maximum scour depth downstream of an apron under submerged wall jets

Abstract: An analysis of laboratory experimental data pertaining to local scour downstream of a rigid apron developed under wall jets is presented. The existing equations for the prediction of the maximum scour depth under wall jets are applied to the available data to evaluate their performance and bring forth their limitations. A comparison of measured scour depth with that computed by the existing equations shows that most of the existing empirical equations perform poorly. Artificial neural network (ANN)- and adapti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Many empirical equations are available in the literature to predict the maximum depth of scour around piers and under wall jets [35][36][37]. Aamir and Ahmad [38] compared the performance of the existing equations using the available laboratory data and concluded that the equation proposed by Dey and Sarkar [15] is superior to others. However, that equation does not account for roughness of the stiff apron and is applicable only to smooth aprons.…”
Section: Estimation Of Maximum Scour Depthmentioning
confidence: 99%
See 1 more Smart Citation
“…Many empirical equations are available in the literature to predict the maximum depth of scour around piers and under wall jets [35][36][37]. Aamir and Ahmad [38] compared the performance of the existing equations using the available laboratory data and concluded that the equation proposed by Dey and Sarkar [15] is superior to others. However, that equation does not account for roughness of the stiff apron and is applicable only to smooth aprons.…”
Section: Estimation Of Maximum Scour Depthmentioning
confidence: 99%
“…Empirical equations were obtained for characteristic lengths of scour hole in non-uniform and uniform sediments, and guidelines were provided for designing a launching apron [16]. Aamir and Ahmad [17,18] investigated experimentally the characteristics of submerged jets causing scour downstream of an apron and developed an empirical equation for the prediction of equilibrium scour depth. Recently, researchers used soft-computing techniques to predict scour downstream of sluice gates and other hydraulic structures [19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Appropriate design of erosion protection works requires thorough study of the scour profile and dimensions, and the flow characteristics within the scour hole. Several studies of scour hole and flow characteristics downstream of sluice gates have been done (Hassan & Narayanan 1985;Chatterjee et al 1995;Balachandar & Kells 1997, 1998Balachandar et al 2000;Dey & Sarkar 2006;Bey et al 2007Bey et al , 2008Farhoudi & Smith 2010;Guan et al 2014;Melville & Lim 2014;Aamir & Ahmad 2015Pandey et al 2015). Different appurtenancese.g., chutes, sills, and baffle blocksare generally placed in stilling basins to stabilize flow by creating turbulence to dissipate energy.…”
Section: Introductionmentioning
confidence: 99%
“…According to Dey & Sarkar (2006), a launching apron (IRC-89 1985) of 18 mm stones downstream of a solid apron on an unconsolidated bed over a length twice the maximum scour depth can reduce scour depth significantly. A comprehensive review of scour due to wall jets was made by Aamir & Ahmad (2016).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, it could be concluded that the empirical models do not experience proper generalization ability for estimating the maximum scour below the PLs. In recent decades, soft computing models such as genetic programming (GP) [4][5][6][7], artificial neural network (ANN) [8][9][10][11], adaptive neuro fuzzy interface system (ANFIS) [12][13][14][15], and regression tree [16,17] were successfully utilized to forecast the scour depth below PLs. It should be noted that the scour rate is dependent on the flow direction, flow characteristics, PL diameter, and sediment properties.…”
mentioning
confidence: 99%